Parameters of crystal and electronic structure and magnetic properties of mechanically alloyed Ni3C cubic carbide - Nakonechna, O.I.; Ivanenko, K.O.; Kuryliuk, A.M.; Belyavina, N.N. (Physics and Chemistry of Solid State, 2021)
The cubic Ni3.3C carbide has been fabricated by mechanical alloying of elemental Ni powder and the multiwalled carbon nanotubes in a high energy planetary ball mill. Crystal structure of carbide obtained belongs to the defective structure of ZnS sphalerite type according to x-ray diffraction data. Parameters of the electronic structure of Ni3.3C were calculated by linearized muffin-tin orbitals method within the plane-wave approximation using as an input the defined parameters of crystal structure. Magnetic properties, such as temperature and field dependences of the magnetic susceptibility of Ni3.3C have been studied. Based on experimental data obtained by studying the crystal structure and magnetic properties of Ni3.3C, as well as on the basis of calculations of electronic structure parameters, a preferred displacement of the carbon atoms in tetrahedral voids of Ni crystal lattice has revealed.